Stunting Countermeasures Model (A Case Study of a Specific Nutrition Intervention Program) - Ari Nofitasari; Islaeli Islaeli; Hasniah Dina (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2025)
Introduction: The prevalence of stunting in Indonesia (24.4%). The data from Southeast Sulawesi Province (2021), showed that the prevalence of stunting included 35.2% in Buton Regency, 30.9% in South Buton, 22.8% in Central Buton, 21,3% Bombana, 20% North Buton, 19,8% East Kolaka, 19.5% Konawe South, 19.3% in Konawe, 17.3% in Muna Regency, 16.4% North Konawe, 14.9% Wakatobi, 13.7% in West Muna, 12.2% Kolaka, 11.1% in Bau-Bau City, 9% in Konawe Island, 9% in North Kolaka, and 5.6% in Kendari City. Kolaka Regency in 2022 showed that the number of stunting toddlers was 620, consisting of 481 toddlers in the short category and 139 toddlers in the very short category. In this study, we aim to see a reduction in the incidence of stunting through specific nutritional interventions. Methods: This research used quantitative methods with a cross-sectional design. The sample in this research was 244 respondents, using a purposive sampling technique. Results: There is a relationship between: socio-economic and the incidence of stunting (X2count = 41.164 > X2Table = 3.841); Exclusive Breastfeeding and the incidence of Stunting (X2count= 18.511 > X2Table = 3.841); breast milk complementary food and the incidence of Stunting (X2count= 5.678 > X2Table= 3.841); immunization and the incidence of Stunting (X2count value = 69.750 > X2Table value = 3.841); the vitamin A capsules and the incidence of Stunting (X2count= 8.001 > X2Table= 3.841); protein intake and the incidence of Stunting (X2count= 3.927 > X2Table= 3.841); energy adequacy figures and Stunting criteria (X2count= 11.759 > X2Table= 3.841); The stunting control model through a combined scenario experienced a decline rate with an optimistic strategy of 1.82%. Conclusion: In conclusion, there was a significant relationship between household socio-economic factors, exclusive breastfeeding, complementary breastfeeding, immunization, vitamin A capsules, protein intake, and energy intake and the incidence of stunting.